Prognostic relevance of MOG antibodies in children with an acquired demyelinating syndrome. (29th August 2017) - Hennes, Eva-Maria; Baumann, Matthias; Schanda, Kathrin; Anlar, Banu; Bajer-Kornek, Barbara; Blaschek, Astrid; Brantner-Inthaler, Sigrid; Diepold, Katharina; Eisenkölbl, Astrid; Gotwald, Thaddäus; Kuchukhidze, Georgi; Gruber-Sedlmayr, Ursula; et al.
Abstract : Objective: To assess the prognostic value of MOG antibodies (abs) in the differential diagnosis of acquired demyelinating syndromes (ADS). Methods: Clinical course, MRI, MOG-abs, AQP4-abs, and CSF cells and oligoclonal bands (OCB) in children with ADS and 24 months of follow-up were reviewed in this observational prospective multicenter hospital-based study. Results: Two hundred ten children with ADS were included and diagnosed with acute disseminated encephalomyelitis (ADEM) (n = 60), neuromyelitis optica spectrum disorder (NMOSD) (n = 12), clinically isolated syndrome (CIS) (n = 101), and multiple sclerosis (MS) (n = 37) after the first episode. MOG-abs were predominantly found in ADEM (57%) and less frequently in NMOSD (25%), CIS (25%), or MS (8%). Increased MOG-ab titers were associated with younger age ( p = 0.0001), diagnosis of ADEM ( p = 0.005), increased CSF cell counts ( p = 0.011), and negative OCB ( p = 0.012). At 24-month follow-up, 96 children had no further relapses. Thirty-five children developed recurrent non-MS episodes (63% MOG-, 17% AQP4-abs at onset). Seventy-nine children developed MS (4% MOG-abs at onset). Recurrent non-MS episodes were associated with high MOG-ab titers ( p = 0.0003) and older age at onset ( p = 0.024). MS was predicted by MS-like MRI ( p < 0.0001) and OCB ( p = 0.007). An MOG-ab cutoff titer ≥1:1, 280 predicted a non-MS course with a sensitivity of 47% and a specificity of 100% and a recurrent non-MS course with a sensitivity of 46% and a specificity of 86%. Conclusions: Our results show that the presence of MOG-abs strongly depends on the age at disease onset and that high MOG-ab titers were associated with a recurrent non-MS disease course.